ANALISIS SUSTAINABLE DEVELOPMENT BERBASIS KOMODITAS TIMAH DI PROVINSI KEPULAUAN BANGKA BELITUNG MENGGUNAKAN PENDEKATAN DATA PANEL - Listiawati, Sitra Wahyu; Wibowo, Aryo Prawoto; Rosyid, Fadhila Achmadi (Jurnal Teknologi Mineral dan Batubara, 2024)
Sustainable development is one of the important aspects of the development of a region. Development planning of a region has many obstacles, one of them is the dependence on a certain sector that becomes a source of regional income, such as the tin mining sector in Bangka Belitung Province. Sustainable development has several goals that are represented by three main aspects; economic, social, and environmental aspects of the six regencies in the Bangka Belitung Island Province. The economic aspect uses Gross Regional Domestic Product data from the tin mining sector, the social aspect uses Human Development Index data, and the environmental aspect uses the Environmental Quality Index data. These three aspects will be used as indicators to obtain the value of the Sustainable Development Index in the Bangka Belitung Islands Province. This study used the panel data method to examine the influence of the tin mining sector as one of the largest contributors to regional income, on sustainable development in the Bangka Belitung Islands Province. The panel data method was used to analyze the economic, social, and environmental aspects of the Sustainable Development Index so that the most influence sustainable development aspect in the Bangka Belitung Islands Province can be identified. The results of this study show that the mining sector  had the least contribution of 0.17 units to the Sustainable Development Index compared to the Human Development Index value of 5.9 units and 0.48 units of the Environmental Quality Index value which represented social and environmental aspects.